Dynamic Tensile Properties and Fracture Evolution Characteristics of Ice-Filled Fissured Red Sandstone - Jiaming Wang; Zilong Zhou; Lingyi Zeng; Jun Hou; Zhen Wang (Rock Mechanics and Rock Engineering, 2026)

Maternal Stress During Pregnancy Induces Higher Anxiety-Like Behavior in Male Mice Offspring Under Acute Stress by Upregulating CRF/CRFR1 and Driving Time-Specific Activation of the MHb-IPN Circuit - Yujie Wang; Jiajia Zhao; Yueyang Wang; Zhixin Du; Li Wang; Zibo Ma; Siyang Sun; Xinyang Qu; Xiaohan Geng; Jiaming Yan; Liping Yang; Junlin Hou (Neuroscience Bulletin, 2026)

Spatial mismatch and inequality between ecological pressure and economic benefits embodied in agricultural trade - Kaige Lei; Jiaming Zhang; Yan Li; Xinhui Feng; Jiayu Yang; Li Hou; Jianguo Liu (Environmental Impact Assessment Review, 2026)

A new matrix propagation method for theoretical analysis of wave propagation in low-temperature gradient layered rock mass with parallel ice-filled joints - Jiaming Wang; Zilong Zhou; Zhen Wang; Jun Hou; Ning Yang; Yaocai Ma (International Journal of Rock Mechanics and Mining Sciences, 2026)

BnaCIPK9 homoeologs mediate the dosage-dependent regulation of seed oil in allotetraploid Brassica napus L - Nan Wang; Jingquan Tang; Xianfei Hou; Chengtao Quan; Jiaming Mai; Chao He; Rundong Chen; Baolong Tao; yuanguo Gu; Donghai Jia; Tingdong Fu; Jitao Zou; et al. (Theoretical and Applied Genetics, 2026)

Different geographical patterns and assembly mechanisms of phytoplankton and benthic diatoms: a case study in a cold temperate wetland cluster - Yongxu Duan; Zhengxun Li; Jiaming Liu; Zheng Hou; Henglin Xiao; Yan Liu; Yawen Fan; Xinxin Lu (Hydrobiologia, 2026)

Modern pollen analysis on peatlands across monsoonal China and its implications for reconstruction - Shu Chen; Mengmeng Wang; Chunmei Ma; Tianyi Tang; Rui Ke; Jiaming Hou; Xinrong Zhang; Zhuo Zheng; Xiayun Xiao; Yan Zhao; Huayu Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Determining the age of Guadalupian extinction by in situ uranium–lead geochronology in regard to middle Permian giant bivalve Alatoconchidae fossils in the Northwest margin of the South China Plate - Xueqin Zhao; Ran Liu; Fudong Wang; Qian Li; Chen Su; Jiaming Ding; Caifu Xiong; Wentao Li; Jianhua Zhang; Keli Hou (Gondwana Research, 2026)

Corrigendum to “Influence of cascade reservoirs on the distribution, transport, and retention patterns of biogenic elements in the Jinsha River” [Sci. Total Environ. 951 (2024) 175535] - Baolong Zhao; Qinghui Zeng; Jianhua Wang; Yunzhong Jiang; Long Yan; Jiaming Hou; Jiaxuan Tang; Fengbo Zhang; Kang Zhao; Xinyu Li; Peng Hu (Science of The Total Environment, 2025)

Exploring the effects of weather-driven dynamics of desiccation cracks on hydrological process of expansive clay slope: Insights from physical model test - Yi Luo; Xinyu Hou; Jiaming Zhang; Yujie Wang; Mingjian Hu; Guosheng Jiang; Chao-Sheng Tang (Journal of Hydrology, 2025)

Enhancing cancer-killing activity of PMN transfusion therapy via apoptotic modulation function of selenium nanoparticles - Chenyu Lin; Jing Wang; Yuqian Zhu; Dachuan Zhang; Xixi Huang; Jiaming Wang; Jianlin Ren; Ming Hou; Mufan Wu; Bing Shen; Bingdi Chen (Chemical Engineering Journal, 2025)

Analytical Model of Passive Heave Compensator Considering Gas Exchange Between Accumulator and Gas Bottles - Yong Zhan; Mengxuan Hou; Yuzhi Yao; Jiaming Jia; Bailin Yi; Dongyue Qu (Journal of Marine Science and Engineering, 2025)
Dynamic response characteristics of the passive heave compensator with auxiliary gas bottles are investigated in this paper. A mathematical model of the passive heave compensator is developed which includes mechanics, hydraulics and pneumatics. The key innovation of the proposed model is that the thermodynamic model of gas exchange between the piston accumulator and the gas bottles is derived and discussed. Meanwhile, a one-dimensional model of the pipeline resistance effect is established to calculate the pressure drop across the oil pipeline. The proposed model is used to evaluate the different design parameters of the passive heave compensator for heavy lifting cranes. A study was conducted to investigate the influence of the design parameters on the effectiveness of the passive compensator to reduce the payload displacement. The simulation results indicated that substantial improvement may be possible by careful design parameter selection and optimization.

Iron-containing tailings catalyst modified by Mn for SCR of NO with NH3 at low temperature: Study of carrier treatment and calcination temperature - Limin Hou; Jiaming Li; Haobo Li; Wenfei Wu (Fuel, 2025)

The energy system transition pathway towards carbon reduction using a model-coupling approach - Jiali Zheng; Xiaoqing Hou; Jiaming Yang; Lianyang Jiao; D’Maris Coffman; Shouyang Wang (Global Environmental Change, 2024)

Influence of cascade reservoirs on the distribution, transport, and retention patterns of biogenic elements in the Jinsha River - Baolong Zhao; Qinghui Zeng; Jianhua Wang; Yunzhong Jiang; Long Yan; Jiaming Hou; Jiaxuan Tang; Fengbo Zhang; Kang Zhao; Xinyu Li; Peng Hu (Science of The Total Environment, 2024)

Nano ZnO modified amorphous carbon materials enabling long-cycle performance and high-capacity for lithium/sodium-ion batteries - Jiaming Liu; Zhen He; Tongfa Zhao; Yuqian Wei; lingpei Hou; Yunfei Song; Yuxin Wang (Chemical Engineering Journal, 2024)

Characteristics and multi-factor mechanisms of dam construction on food web structure in cold-region rivers - Jiaming Hou; Qinghui Zeng; Peng Hu; Yunzhong Jiang; Yinglan A; Qin Yang; Baolong Zhao; Huan Liu; Zefan Yang; Xiaohui Qu (Journal of Hydrology, 2024)

A shining transmutation of lignin into multicolor carbon dots via the dynamic solvent-fractionation engineering - Xinyan Hou; Jikun Xu; Pengfei Zhou; Lin Dai; Jiaming Zhang; Xiao Xiao; Kaifu Huo (Chemical Engineering Journal, 2023)

Quality retention and delay postharvest senescence of figs (Ficus carica L.) using 1-methylcyclopropene and modified atmosphere packaging during cold storage - Cailian Wang; Jiaming Du; Dehua Hou; Xiaohong Guo; Qianting Liu; Linwen Liu; Yu Fang; Liping Kou (Food Bioscience, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Study on mechanical properties and elasto-brittle-plastic constitutive model of hard brittle rock based on conventional triaxial test - Xinxin Fang; Han Tong; Jiaming Feng; Yanqiu Wang; Xiaowei Ni; Shaoyong Hou; Kang Bie (Arabian Journal of Geosciences, 2022)

Role of rgsA in Oxidative Stress Resistance in Pseudomonas aeruginosa - Shuyi Hou; Jiaqin Zhang; Xiaobo Ma; Qiang Hong; Lili Fang; Gangsen Zheng; Jiaming Huang; Yingchun Gao; Qiaoli Xu; Xinguo Zhuang; Xiuyu Song (Current Microbiology, 2021)

SMAD4 mutations and cross-talk between TGF-β/IFNγ signaling accelerate rates of DNA damage and cellular senescence, resulting in a segmental progeroid syndrome—the Myhre syndrome - Renuka Kandhaya-Pillai; Deyin Hou; Jiaming Zhang; Xiaomeng Yang; Goli Compoginis; Takayasu Mori; Tamara Tchkonia; George M. Martin; Fuki M. Hisama; James L. Kirkland; Junko Oshima (GeroScience, 2021)

Corrosion Mechanism of 5083 Aluminum Alloy in Seawater Containing Phosphate - Jiaming Wang; Haodong Yang; Min Du; Jian Hou; Wenshan Peng; Cunguo Lin (Journal of Ocean University of China, 2021)

Gene polymorphism of chalcone isomerase influence the accumulation of flavonoids in licorice (Glycyrrhiza spp.) - Xiaodong Zhang; Shaokai Tian; Lin Qi; Wendong Li; Jiaming Hou; Lin Yang; Zhixin Zhang; Ying Liu (Genetic Resources and Crop Evolution, 2021)

Safety Evaluation of Sevoflurane as Anesthetic Agent in Mouse Model of Myocardial Ischemic Infarction - Xiang Cheng; Jianglong Hou; Jiaming Liu; Xiaorong Sun; Qin Sheng; Pengfei Han; Y. James Kang (Cardiovascular Toxicology, 2017)